2017
DOI: 10.1161/circulationaha.116.025158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rosuvastatin on Carotid Intima-Media Thickness in Children With Heterozygous Familial Hypercholesterolemia

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01078675.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 19 publications
2
24
0
3
Order By: Relevance
“…IMT is a reliable marker of early atherosclerosis, is an established risk factor for incident cardiovascular acute events, and is used to evaluate the global cardiovascular risk [ 32 ]. Carotid IMT has been frequently monitored in interventional studies to evaluate the efficacy of several drugs in terms of cardiovascular protection [ 33 35 ]. IMT was inversely and strongly associated with wall shear stress [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…IMT is a reliable marker of early atherosclerosis, is an established risk factor for incident cardiovascular acute events, and is used to evaluate the global cardiovascular risk [ 32 ]. Carotid IMT has been frequently monitored in interventional studies to evaluate the efficacy of several drugs in terms of cardiovascular protection [ 33 35 ]. IMT was inversely and strongly associated with wall shear stress [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This work provides another argument for introducing screening programs because, even in children with no signi cant morphological changes, arterial wall function can be already impaired. Diagnosis of subclinical arterial wall stiffening might improve risk strati cation and clinical management in FH patients [13,19].…”
Section: Discussionmentioning
confidence: 99%
“…A mean LDL-C reduction of 41% after 2 years of treatment with rosuvastatin was associated with a significant reduction in the progression of carotid atherosclerosis. 77 Moreover, the 10-year follow-up of children with mean age 12 years old treated with pravastatin during 2 years showed that the statin treatment initiated in childhood normalizes the carotid intima media thickness in the young adults (mean age 24 years old). 78 Recently, the 20-year follow-up of this population has been published comparing the incidence of ASCVD among these patients that started statins since childhood and their affected parents, assuming that parents started statin treatment later in life.…”
Section: Treatment Of Children Living With Fh (Table 2)mentioning
confidence: 99%